Plant cover and hydrological response in a seasonally dry tropical forest (SDTF) - Eunice Maia Andrade; Maria Elinalda Ribeiro Costa; Júlio César Neves dos Santos; Helba Araujo de Queiroz Palácio; Jacques Carvalho Ribeiro Filho (Agro@mbiente On-line)
The scarcity of information on the processes of rainfall-flow limits understanding of the hydrology of dry regions of the world. In order to minimise the problem, this study was developed to investigate the influence of the characteristics of rainfall events and plant cover on the effective precipitation (Pe) in a seasonally dry tropical forest (SDTF) in the Northeast of Brazil. The study was carried out in two paired watersheds, one with SDTF under regeneration for 35 years (CR35) and the other under thinned SDTF for 5 years (TC). A historical series of five years (2009-2013) was analysed, with a total of 203 rainfall events, where only those rainfall events that generated a Pe > 1.0 mm were considered. CR35 had a greater number of Pe events (47) than TC (35). Rainfall depth and intensity were the factors that best explained the effective precipitation under both types of vegetation cover. The influence of herbaceous vegetation on the reduction of surface runoff was demonstrated by the smaller runoff depth and the greater potential for soil water storage in the watershed under thinned Caatinga. This fact leads to the conclusion that the technique of thinning is suitable management for Caatinga vegetation, and is capable of promoting the retention of soil water.